Cathode Materials: Ni and Co Segregations on Selective Surface Facets and Rational Design of Layered Lithium Transition‐Metal Oxide Cathodes (Adv. Energy Mater. 9/2016). Issue 9 (11th May 2016) - Yan, Pengfei; Zheng, Jianming; Zheng, Jiaxin; Wang, Zhiguo; Teng, Gaofeng; Kuppan, Saravanan; Xiao, Jie; Chen, Guoying; Pan, Feng; Zhang, Ji‐Guang; Wang, Chong‐Min
Abstract : In article number 1502455, Ji‐Guang Zhang, Chong‐Min Wang and co‐workers show that Ni tends to segregate on the (200) facet and form spinel‐like structures, while Co segregates predominantly on the (20‐2) facet to form rock salt structures. The cover image depicts the distinctive crystallographic surface selective segregation of Ni and Co in lithium transition metal oxides as a cathode for rechargeable lithium ion batteries.